The Relationship of Marketing Strategies With the Interest of Re-Visit Patients of the Heart Policy Clinic in the Regional General Hospital of Dr. Rasidin Padang City - Ashifa Rozika; Asmawati; Meyi Yanti (STIKes Alifah Padang, 2023)
This study aims to determine the relationship between marketing strategy and interest in repeat visits of outpatient at the Cardiac Polyclinic at Dr. Rasidin Hospital, Padang City. The research method used is quantitative by design cross sectional study. The sample in this study amounted to 96 respondents. The results showed that 85.4% of patient repeat visits were in the category of interest, 54.2% of the product marketing strategy was in the good category, 56.2% in the place marketing strategy was in the good category, 57.3% in the price marketing strategy was in the good category, 54.2% was the promotion marketing strategy was in the good category. Statistical test results show that there is a significant relationship between place marketing strategy (p=0,011), promotion marketing strategy (p=0,003) and obtained marketing promotion strategy with a value of OR = 9,375.